Quality of care index and gender disparity ratio for stroke and its subtypes from the Global Burden of Disease Study 2021 - Aqian Yu; Jingjing An (PLoS ONE, 2026)
Objectives This study aims to explore the quality of care index (QCI) for stroke, intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH), and ischemic stroke (IS) across nations, genders, age groups, and periods from the Global Burden of Diseases Study (GBD) 2021. Methods Prevalence, incidence, and years lived with disability (YLDs) rates were used to estimate the burden. Estimated annual percentage change (EAPC) was utilized to evaluate trends. QCI was calculated through principal component analysis. Gender disparity ratio (GDR), a ratio of female QCI and male QCI, was used to evaluate the disparity. Spearman correlation analysis was performed to investigate the association between QCI, GDR, and SDI. Results The age-standardized prevalence, incidence, and YLDs rates for stroke, ICH, SAH, and IS decreased from 1990 to 2021 (EAPC<0). The QCI showed an increased trend for stroke (51.6 vs 65.7) worldwide. The GDR for stroke, ICH, and IS improved (near one), whereas the GDR of IS experienced a slight increase. The values of QCI increased with the rising of SDI for stroke, ICH, SAH, and IS. However, the values of GDR decreased with the increasing of SDI for stroke, ICH, and IS. Considerable disparities between countries, genders, and age groups concerning the QCI and GDR were observed. Conclusion The QCI and GDR improved from 1990 to 2021 among most countries and regions. Both QCI and GDR were associated with SDI. Significant disparities between countries, genders, and age groups for QCI and GDR should be addressed.